New genealogies and the courage of truth: Toward an ethics of adversarial public educational scholarship and policy activism - Burns, James P.; Green, Colin D.; Nolan, Jaime (Education Policy Analysis Archives, 2018)
Science denial in the post-truth era is driven by both the rejection of empirical science and the fraudulent use of scientific language. Education policy based on junk science produced by philanthrocapitalists depoliticizes political questions by relocating complex legislative and policy issues from the realm of political and philosophical discourse to that of scientific rationality using metrics and methods that are themselves fatally flawed. Dominant configurations of institutional power also attack scholarship that both debunks spurious causal claims and establishes causal links to existential crises, which in both cases inconveniences the neoliberal capitalist project. We discuss the methodological implications of education research as the counter-conduct of policy advocacy against power claims based on both the rejection of empirical science and the production of junk science. We both discuss and model Foucault’s tactic of genealogy and his analysis of parrhēsia, or truth telling, through creating an imperfect, preliminary genealogy of the “new” post-truth era, which contextualizes contemporary technologies of alternative facts in the history of public relations and propaganda that extend to the early 20thcentury. The methodological and political tactic of genealogy could be a move toward a new ethics of adversarial public scholarship that seeks to reconfigure what counts as scholarship in academia, itself a rationalizing disciplinary institution. Considering the moment, the study of power, the academy’s roles both in subverting and perpetuating it, and the necessity of epistemological and methodological counter-conduct have perhaps never been more important.